Climate Change Impacts on Future Solar Photovoltaic System Performance and Power Output in Libya - Nasr Alhusein; Ali, Abdussalam (AlQalam Journal of Medical and Applied Sciences, 2022)
Climate change has the potential to have a significant impact on renewable energy generation. The current state of the art in forecasting future renewable energy output has centered on regional climate prediction. However, owing to the complexity of climate models, regional climate prediction is fraught with uncertainty. This research provides a new methodology to predict the impact of the climate changes on the Photovoltaic solar system generation by using the extrapolation method for the historical data from NASA organization for the irradiation and the temperature from the year 1880 and extended to 2100. In this paper, the energy outputs of one of the solar power stations expected to be established in Libya, located in the Libyan city of Tajoura, were evaluated and predicted, specifically inside the headquarters of the Centre for Solar Energy Research and Studies. The Simulink Model of the power station was created using the Matlab program. The results showed that during the coming years, the temperature will rise by about three degrees Celsius, and at the same time the solar radiation will decrease and the output power generated by solar energy will decrease with it.